Network meta-analysis of the effects of different dietary patterns on patients with metabolic syndrome - Lv, Jie; Jiao, Shiyu; Li, Wenjing; Ding, Shuo; Ma, Li; Zhang, Qian (Frontiers in Nutrition, 2025)
BackgroundDietary patterns play an important role in the management of metabolic syndrome (MetS). Previous meta-analyses have shown that the ketogenic diet, the Dietary Approaches to Stop Hypertension (DASH) diet, the vegetarian diet, the Mediterranean diet, the low-fat diet, and the low-carbohydrate diet are beneficial for patients with MetS, but there is still a lack of direct comparison of the intervention effects of the above six dietary patterns.ObjectiveThis study aimed to explore the intervention efficacy of different dietary patterns on MetS and to evaluate and compare the corresponding effects.MethodsA comprehensive search was carried out in electronic databases such as Embase, Cochrane Library, PubMed, Web of Science, Scopus, CNKI, Wanfang, VIP, and CBM. The search covered studies published from the establishment of the databases up to 1 April 2025, with a focus on dietary patterns that can improve metabolic syndrome. A network meta-analysis was carried out using Stata 16.0 software.ResultsEventually, 26 randomized controlled trials were included, involving 2,255 patients. The results of the network meta-analysis showed that the DASH diet [MD = −5.72, 95% CI (−9.74, −1.71)] and the vegan diet [MD = −12.00, 95% CI (−18.96, −5.04)] were more effective in reducing the waist circumference of patients with MetS than the control diet group. In terms of lowering blood pressure, the DASH diet [MD = −5.99, 95% CI (−10.32, −1.65)] and the ketogenic diet [MD = −11.00, 95% CI (−17.56, −4.44)] were more effective in reducing systolic blood pressure in patients with MetS than the control diet group. The ketogenic diet [MD = −9.40, 95% CI (−13.98, −4.82)] was more effective in reducing diastolic blood pressure in patients with MetS than the control diet group (p < 0.05). According to the ranking results, a vegan diet is the best choice in terms of reducing waist circumference and increasing high-density lipoprotein cholesterol levels. The ketogenic diet is highly effective in lowering blood pressure and triglyceride levels. The Mediterranean diet is highly effective in regulating fasting blood glucose.ConclusionThe current evidence indicates that the vegan diet, the ketogenic diet, and the Mediterranean diet might have more pronounced effects in ameliorating MetS. Further high-quality research is needed to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier (CRD420251052075).